2018
DOI: 10.1016/j.ygyno.2018.07.024
|View full text |Cite
|
Sign up to set email alerts
|

BRCA germline mutations in an unselected nationwide cohort of Chinese patients with ovarian cancer and healthy controls

Abstract: We recommend BRCA testing to all Chinese OC patients and those general Chinese who have family members with hereditary breast and ovarian related cancer (HBOC)-related cancers. Variants carriers would not only benefit from early prevention of OC but also for the medical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 31 publications
(39 reference statements)
7
36
2
1
Order By: Relevance
“…The mutation rate of BRCA1/2 in our ovarian cancer subgroup was slightly higher than that in other studies that found BRCA1/2 deleterious mutations with rates of 13% to 15% . Overall, BRCA1/2 mutation accounted for 86% of total mutations in hereditary ovarian cancer, and the BRCA1 mutation rate was more pronounced than the BRCA2 in ovarian cancer patients, which is similar to the results from both Li et al (2018, n = 1331, BRCA1 for 17.1% and BRCA2 for 5.3%) and Norquist et al (2016, n = 1915, BRCA1 for 9.5% and BRCA2 for 5.1%). Apart from the B RCA1/2 mutation, 0.9% of the subgroup carried BRIP1 mutation (BRCA1‐interacting protein C‐terminal helicase 1), which is comparable to other studies in which the prevalence ranges from 0.8% to 1.5% .…”
Section: Discussionsupporting
confidence: 87%
“…The mutation rate of BRCA1/2 in our ovarian cancer subgroup was slightly higher than that in other studies that found BRCA1/2 deleterious mutations with rates of 13% to 15% . Overall, BRCA1/2 mutation accounted for 86% of total mutations in hereditary ovarian cancer, and the BRCA1 mutation rate was more pronounced than the BRCA2 in ovarian cancer patients, which is similar to the results from both Li et al (2018, n = 1331, BRCA1 for 17.1% and BRCA2 for 5.3%) and Norquist et al (2016, n = 1915, BRCA1 for 9.5% and BRCA2 for 5.1%). Apart from the B RCA1/2 mutation, 0.9% of the subgroup carried BRIP1 mutation (BRCA1‐interacting protein C‐terminal helicase 1), which is comparable to other studies in which the prevalence ranges from 0.8% to 1.5% .…”
Section: Discussionsupporting
confidence: 87%
“…The frequency of BRCA1/2 mutations was 23.07% in the ovarian cancer only subgroup, 15.38% for BRCA1 and 7.69% for BRCA2. Overall, BRCA1/2 accounted for 86% in hereditary ovarian cancer, and the BRCA1 mutation rate was more pronounced than the BRCA2 mutation rate in ovarian cancer patients, similar to both Ang Li et al (22) (2018, n = 1331, BRCA1 for 17.1% and BRCA2 for 5.3%) and Norquist et al (23) (2016, n = 1915, BRCA1 for 9.5% and BRCA2 for 5.1%). Interestingly and noteworthy, ovarian cancer carried BRCA1/2 mutations in China was slightly higher than expected.…”
Section: Comparison Of Mutation Frequency With Previous Studiessupporting
confidence: 75%
“…Previously, BRCA1 c.5470_5477del was reported as a high‐frequency recurrent pathogenic variant in Chinese BC patients and ovarian cancer patients . Only one previous study performed a haplotype analysis for BRCA1 c.5470_5477del, in which three independent families shared the same haplotype, whereas two additional BC patients had similar but not exactly the same haplotype .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, BRCA1 c.5470_5477del was reported as a highfrequency recurrent pathogenic variant in Chinese BC patients and ovarian cancer patients. 16,19,24 Only one previous study performed a haplotype analysis for BRCA1 c.5470_5477del, in which three independent families shared the same haplotype, whereas two additional BC patients had similar but not exactly the same haplotype. 16 Because of the small sample size (n = 489) and mixed ethnicity of the subjects, this previous study was not sufficient to demonstrate whether BRCA1 c.5470_5477del is a Chinese Han founder mutation.…”
Section: Discussionmentioning
confidence: 99%